The complete chloroplast genome of Aquilegia barnebyi, a basal eudicot species - Hui Huang (Mitochondrial DNA. Part B. Resources, 2020)
Aquilegia barnebyi, belonging to the genus Aquilegia (Ranunculaceae), is a member of basal eudicot species. In this study, we obtained the complete chloroplast (cp) genome of A. barnebyi. The genome size is 161,954 bp with a GC content of 38.98%. A total of 113 unique genes including 79 protein-coding genes, 30 tRNA genes, four rRNA genes were annotated. The large single-copy region and small single-copy region contains 91,250 bp and 17,359 bp, respectively. The inverted repeat regions are 26,671 bp in length. The phyologenetic analysis indicated that A. barnebyi had a close relationship with A. coerulea. And four species in genus Aquilegia formed a monophyletic group with high support value. The availability of A. barnebyi cp genomic resources will greatly helpful for taxonomy, phylogeny and conservation genetic studies of basal eudicot specie.